How does information on the harms and benefits of cervical cancer screening alter the intention to be screened? A randomized survey of Norwegian women - Iyer, Anita L. (Eur J Cancer Prev, 2019)
OBJECTIVES: Cervical cancer is the 13th most frequent cancer among women in Norway, but the third most common among women aged 25–49 years. The national screening program sends information letters to encourage screening participation. We aimed to evaluate how women’s stated intention to participate in screening and pursue treatment changed with the provision of additional information on harms associated with screening, and to assess women’s preferences regarding the timing and source of such information. METHODS: We administered a web-based questionnaire to a panel of Norwegian women aged 25–69 years, and randomized into 3 groups based on when in the screening process additional information was introduced: 1) invited for routine screening, 2) recommended an additional test following detection of cellular abnormalities, and 3) recommended precancer treatment. A fourth (control) group did not receive any additional information. RESULTS: Among 1,060 respondents, additional information did not significantly alter women’s stated intentions to screen. However, it created decision uncertainty when treatment was recommended (8.76–9.09 versus 9.40; 10-point Likert scale; p=0.004). Over 80% of women favored getting information on harms and 59% preferred that information come from a qualified public health authority. Nearly 90% of women in all groups overestimated women’s lifetime risk of cervical cancer. CONCLUSION: Additional information on harms did not alter Norwegian women’s stated intention to screen for cervical cancer; yet, it resulted in greater decision uncertainty to undergo precancer treatment. Incorporating information on harms in invitation letters is warranted, as it would increase women’s ability to make informed choices.